Human industrial robot collaboration - development and application of simulation software. (2015) - Ore, Fredrik; Hanson, Lars; Delfs, Niclas; Wiktorsson, Magnus
Human industrial robot collaboration (HIRC) aims to combine the benefits of industrial robots with humans in production environments. This is a growing research field where most work focuses on the safety aspects, while little research is performed on simulation and visualisation. The aim of this paper is to present demonstrator software for simulation, visualisation and evaluation of human industrial robot collaboration. Two simulation software products were combined to reach this goal. The new tool was then applied to two industrial assembly cases where productivity and biomechanical loads on humans were calculated. The resulting demonstrator software simulates and visualises human industrial robot collaboration. The quantitative output from the simulation makes it possible to compare HIRC, manual and robotic assembly stations in terms of productivity and ergonomics.